Assessment on the efficiency of flood mitigation measures - Zuriyati Yusof; Noor Aida Saad; Muhamad Syafiq Abd Rahim; Purany Kalimuthu (Penerbit Universiti Kebangsaan Malaysia, 2023)
Storms and floods are frequent occurrences that can disrupt communities and harm ecosystems. An effective flood management plan requires a decision-making process that balances financial, social, and environmental benefits. This paper provides an overview of a study that applied a decision-making process using engineering analysis to determine the most effective approach in selecting the most effective flood mitigation measures. This study used hydrodynamic modelling to determine the effectiveness of proposed measures, such as the construction of a flood wall and river improvement works. The results showed that the combination of both measures could provide 100 ARI level protection, reducing the flood area from 6.11 km2 to 0.00 km2 areas without flooding. The study highlights the importance of considering financial, social, and environmental benefits in selecting effective flood mitigation measures.